Incidence of Deep Vein Thrombosis in Spine Surgery Patients at a Tertiary Care Hospital - Rakan Aldusari (Journal of Spine Practice)
Introduction: The prevalence of deep venous thrombosis (DVT) and pulmonary embolisms (PE) has not been established accurately. Reported literature suggests an incidence rate of either DVT or PE ranging from 0.27% to as high as 60% in special cases. We aimed to discern the incidence rate in our local population post spinal surgery.